Tannic Acid as a Versatile Template for Silica Monoliths Engineering with Catalytic Gold and Silver Nanoparticles - Irina Postnova; Yury Shchipunov (Nanomaterials, 2022)
Tannic acid in alkaline solutions in which sol-gel synthesis is usually performed with tetraethoxysilane is susceptible to various modifications, including formation of reactive radicals, oxidation under the action of atmospheric oxygen, self-association, and self-polymerization. Here, a precursor with ethylene glycol residues instead of ethanol was used, which made it possible to synthesize bionanocomposites of tannic acid and silica in one stage in neutral media under normal conditions without the addition of acid/alkali and organic solvents. Silica was fabricated in the form of optically transparent monoliths of various shapes with 2–4 nm pores, the radius of which well correlated with the size of a tannic acid macromolecule in a non-aggregated state. Polyphenol, which was remained in pores of silica matrix, served then as reducing agent to synthesize in situ gold and silver nanoparticles. As shown, these Au@SiO2 and Ag@SiO2 nanocomposites possessed localized surface plasmon resonance and high catalytic activity.